Analisis Dampak Kebijakan Tarif Safeguard terhadap Impor Kain Tenun dari Kapas di Indonesia Tahun 2008-2022 dengan Pendekatan ARIMA Intervention Model - Khoirunisa Maula Izzaty; Siskarossa Ika Oktora (Universitas Sebelas Maret, 2025)
The increase in the price of cotton raw materials as well as the low quality of products and productivity of the domestic industry has increased imports of woven fabric from cotton in Indonesia. The increase in imports resulted in serious losses to the domestic industry. Indonesian Textile Association submitted a petition to investigate imports of cotton woven fabric and resulting in a decision to implement a safeguard tariff policy on imports of cotton woven fabric. This research aims to analyze the impact of safeguard tariffs and the elimination of safeguard tariffs on the volume of imports of cotton woven fabrics. The method used is ARIMA multi-input intervention with interventions in the form of a safeguard tariff policy for 2011-2014, elimination of safeguard tariffs for 2014-2020, and a safeguard tariff policy for 2020-2022. The research results show that the safeguard policy in 2011-2014 and 2020-2020 had an impact on reducing the volume of imports of woven cotton fabrics. Meanwhile, the elimination of the safeguard policy in 2014-2020 had the impact of increasing the volume of imports of cotton woven fabrics. The results of this research can be used as material for the government's evaluation regarding safeguard tariff policies in protecting the domestic cotton woven fabric industry. Keywords: ARIMA intervention, cotton, woven fabric